2021
DOI: 10.48550/arxiv.2104.11299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global well-posedness of the Cauchy problem for the Jordan--Moore--Gibson--Thompson equation with arbitrarily large higher-order Sobolev norms

Abstract: In this paper, we consider the 3D Jordan-Moore-Gibson-Thompson equation arising in nonlinear acoustics. First, we prove that the solution exists globally in time provided that the lower order Sobolev norms of the initial data are considered to be small, while the higher-order norms can be arbitrarily large. This improves some available results in the literature. Second, we prove a new decay estimate for the linearized model and removing the L 1 -assumption on the initial data. The proof of this decay estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Let us turn to the JMGT equation (3), which has been studied by [18,19,24,3,25] and references therein. Additionally, the semilinear MGT equation in the conservative case for R n has been investigated by [5,6].…”
Section: Background Of the Mgt And Jmgt Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Let us turn to the JMGT equation (3), which has been studied by [18,19,24,3,25] and references therein. Additionally, the semilinear MGT equation in the conservative case for R n has been investigated by [5,6].…”
Section: Background Of the Mgt And Jmgt Equationsmentioning
confidence: 99%
“…Concerning the Cauchy problem for (3) in the dissipative case, [24] demonstrated global (in time) well-posedness result in 3D by using higher-order energy methods together with a bootstrap argument, and derived some decay estimates of solutions with weighted L 1 assumption on initial data. Quite recently, the author of [25] improved the global (in time) existence result for 3D, where the smallness assumption for higher-order regular data was removed, whose idea is to utilize negative Sobolev spaces. To the best of the author's knowledge, the application of energy method to prove global (in time) existence of solutions required some suitable constructions of energy.…”
Section: Background Of the Mgt And Jmgt Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [28] demonstrated global (in time) well-posedness result in three-dimensions by higher-order energy methods together with a bootstrap argument, and derived some decay estimates of solutions. Quite recently, the author of [29] improved the global (in time) existence result in [28] for three-dimensions, where the smallness assumption for higher-order regular data was dropped in the framework of Sobolev spaces with negative index. So far the sharp estimates and asymptotic profiles of solutions are still open, especially, in the physical dimensions n = 1, 2, 3.…”
Section: Mathematical Researches On the Jmgt Equationmentioning
confidence: 99%
“…Concerning the MGT equation and the JMGT equation, some qualitative properties of solutions (well-posedness, stabilities, decay estimates, singular limits, inviscid limits and asymptotic profiles) have been deeply analyzed. We refer interested readers to [28,29,36,11,42,2,30,43,3,9,10,8,7,31,44] and references therein.…”
Section: Background Of Acoustic Waves In Non-hereditary Fluidsmentioning
confidence: 99%